2019
DOI: 10.1073/pnas.1905462116
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic gasket mutation produces gating pore currents in closed human voltage-gated proton channels

Abstract: The hydrophobic gasket (HG), a ring of hydrophobic amino acids in the voltage-sensing domain of most voltage-gated ion channels, forms a constriction between internal and external aqueous vestibules. Cationic Arg or Lys side chains lining the S4 helix move through this “gating pore” when the channel opens. S4 movement may occur during gating of the human voltage-gated proton channel, hHV1, but proton current flows through the same pore in open channels. Here, we replaced putative HG residues with less hydropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 77 publications
(145 reference statements)
2
49
0
Order By: Relevance
“…A similar observation was made by using electron paramagnetic resonance (EPR) measurements on hHv1 at 0 mV (45). This shift puts V178 in better alignment with F150 to form a hydrophobic gasket, a finding consistent with a recent study that probed the gasket stability in the closed state (43). The S4 helix gating charges are straddling this position with the lower two arginine residues, R208 and R211, sitting closer to the intracellular side of the pore, with R205 just above F150.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A similar observation was made by using electron paramagnetic resonance (EPR) measurements on hHv1 at 0 mV (45). This shift puts V178 in better alignment with F150 to form a hydrophobic gasket, a finding consistent with a recent study that probed the gasket stability in the closed state (43). The S4 helix gating charges are straddling this position with the lower two arginine residues, R208 and R211, sitting closer to the intracellular side of the pore, with R205 just above F150.…”
Section: Discussionsupporting
confidence: 85%
“…This can be achieved by using engineered cysteine cross-links through a metal-ion bridge, which allows for the protein to maintain its physiological conformation (38)(39)(40)(41). Residue V109 in S1 has been experimentally shown to face the VSD permeation pathway (42,43), and in an earlier up-state model of hHv1 (28), it was predicted to be in the vicinity of F150. We expressed in Xenopus oocytes a monomeric version of Hv1 (21, 44) (see Materials and Methods for details), in which the only endogenous cysteine in the VSD, C107, was replaced by an alanine (background) or versions of the same channel containing one single amino-acid substitution, V109C or F150C, or the double substitution V109C/F150C.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it is interesting to note that cysteine mutation at positions V157 and V164 perturbed channel function in the monomer, but not the dimer (Table 1). Residues V157 and V164 were shown to be part of the two hydrophobic layers constricting the inner VSD water-filled crevice (24,35), the opening of which seems to be required to allow proton permeation (35,43). This suggests that at least two parameters control channel opening: The interprotomer interface (see below) and the intraprotomer hydrophobic layers.…”
Section: Resultsmentioning
confidence: 98%
“…The existing crystal structure is a chimera of mouse H V 1, with its N terminus truncated, its C terminus replaced by a leucine-zipper motif of the transcriptional activator GCN4 from Saccharomyces cerevisiae , and with a section of C. intestinalis voltage-sensing phosphatase spliced in from the middle of S2 to the middle of S3. It has been suggested that insertion of the CiVSP peptide at the inner side of S2-S3 resulted in S3 in the crystal structure being too low by one helical turn ( DeCoursey, 2015a ; Li et al, 2015 ; Banh et al, 2019 ). Thus, the high-affinity Zn 2+ binding observed here between V116H and D185 supports the Li et al closed state model.…”
Section: Discussionmentioning
confidence: 99%